2008
DOI: 10.1016/j.urology.2007.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Mechanical Imaging: A New Method for Prostate Assessment

Abstract: Objectives-To evaluate the ability of Prostate Mechanical Imaging (PMI) technology to provide an objective and reproducible image and to assess the prostate nodularity.Methods-The PMI device developed by Artann Laboratories was evaluated in a pilot clinical study. For the 168 patients (ages 44 to 94) presented to an urologist for prostate evaluation, PMIproduced images and assessment of prostate size, shape, consistency/hardness, mobility, nodularity, and was compared with digital rectal examination (DRE) find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…[27]. But, in most applications, an accurate and comprehensive characterization of tissue mechanical properties is impractical, and simple means provide reproducible tissue characterization [911, 23]. Therefore, we are using a simplest non-linear tissue model for vaginal tissue, which allows practical comparison of tissue elasticity in terms of a single parameter such as Young’s modulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27]. But, in most applications, an accurate and comprehensive characterization of tissue mechanical properties is impractical, and simple means provide reproducible tissue characterization [911, 23]. Therefore, we are using a simplest non-linear tissue model for vaginal tissue, which allows practical comparison of tissue elasticity in terms of a single parameter such as Young’s modulus.…”
Section: Discussionmentioning
confidence: 99%
“…The current increasing number of publications on elastography covers practically all key human organs [810]. Tactile imaging, a branch of elasticity imaging, yields a tissue elasticity map, similarly to other elastographic techniques [912]. At the same time, tactile imaging most closely mimics manual palpation because the tactile imaging probe with a pressure sensor array mounted on its face acts similarly to human fingers during a clinical examination by slightly compressing soft tissue with the probe and detecting the resulting changes in the pressure pattern on the tissue surface.…”
Section: Introductionmentioning
confidence: 99%
“…Dur ing the previous two de cades, advances in in stru men ta tion and mod el ing have led to improvements in elas ticity im ag ing and its in ter pre ta tion for dis crim i nat ing be nign from ma lig nant breast le sions, 1,2 stag ing liver fi bro sis, 3,4 mon i tor ing tu mor ab la tion, 5 as sess ing myo car dial func tion, 6,7 screening for pros tate can cer 8 and prob ing neurodegenerative pro cesses in the hu man brain. 9 The di ag nos tic in for ma tion pro vided by elas tic ity im ag ing orig i nates with the im por tant role of the microscopic cel lu lar mechanoenvironment in es tab lish ing ho meo sta sis and regulating dis ease pro gres sion.…”
Section: Introductionmentioning
confidence: 99%
“…Different MI systems have been created for imaging of the breast [266, 267], prostate [268270], and vagina [271]. It is shown that the potential of MI is not limited only to cancer detection but also may provide the differentiation between malignant and benign lesions [267].…”
Section: Elasticity Imaging Methodsmentioning
confidence: 99%